Microservice Testing Approaches: A Systematic Literature Review - Ghani, Israr; Wan-Kadir, Wan M.N; Mustafa, Ahmad; Imran Babir, Muhammad (International Journal of Integrated Engineering, 2019)
Testing is a crucial part of each code development method to which organizations devote extensive time and effort. The ever-changing industry needs of business necessitate that experts adopt and support themselves to meet the requirements in microservice testing, and in the process of doing so, contribute escalation to newer approaches and essential techniques of architecture in microservice testing from the perspective of microservice testing, the advancement of â€œmicroserviceâ€ is the result of such an activity to make the testing quality better and its impact penetrates down to the quality assurance teams. Working on testing microservice has become a newer structure of this testing architecture. This study explains the challenges that the testing world has to deal with and the effective strategies that can be predicted to overcome them while testing for applications and its design with a microservice testing approaches. This study can also serve as a guide to anyone who wants apparition into microservices and would like to know more about microservice. Testing approaches that can be developed and successfully applied while working within such a landscape. However, one of the major advantages of using microservice that it offers, efficient, flexible, effective, reusability mechanism. Furthermore, it is a secure way to reduce the development and testing time and cost. The security, performance, traceability, compatibility, complexity, effectiveness and scalability become some of the major concerns when testing approaches, frameworks, tools and models are applied for each microservice repository and no previous research addresses these concerns. In this review, we present some testing approaches, frameworks, tools and models to address all these concerns.